Formulation and Assessment of Delayed/Slow-Release Diclofenac Sodium Edible Organogel Utilizing Low Molecular Weight Organogelators - Zahraa Yhaya Aziz; Masar Basim Mohsin; Marwa Hazim Jasim (Iraqi Journal of Pharmaceutical Sciences, 2023)
Organogel as a system was to estimate its capacity to delay and slow the drug release in the duodenum. The gelators, 12HSA (12-hydroxystearic acid), span 60. span 40 were used; the castor oil (CO) and anise oil (AO) also represented the liquid phase. To achieve the goal of this work was by using diclofenac sodium (DS). Organogels specifications were by estimating thermal attitude using tabletop rheology and differential scanning calorimetry (DSC). The organogel strength study was by applying oscillatory rheology tests the amplitude sweep and the frequency sweep. Realizing the morphology of the organogel was done utilizing an optical microscope. CO and AO binding capacity was also manifested. The transition temperatures for all organogels were reversible. Imaging demonstrated spherulites aggregates for organogels of 12HSA and span 40 in CO and AO while span 60 organogels in both oils existed as fibers aggregates. Furthermore, organogels exhibited viscoelastic characteristics as 20 wt% 12HSA in both oils were frequency-independent. The results revealed that the HPMC capsule containing the organogel resisted the dissolution in the acidic media for two hours. Moreover, organogels slowed the release of DS for 24 hours in an alkaline medium. Finally, all the selected organogel in CO exhibited a high oil binding capacity.